Pesantren dan Disabilitas: Praktik Sosial dan Dinamika Pendidikan Anak Berkebutuhan Khusus - Abdulloh Hadziq; Raharjo; Muhammad Sulthon; Nasihun Amin (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2024)
Inclusive education, which provides access to education for children with special needs, is greatly needed in society. However, to this day, the availability of suitable education for children with special needs remains limited. On the other hand, pesantren, as a unique educational institution in Indonesia, holds great potential for developing inclusive education. This study aims to explore the implementation of inclusive education in pesantren through a phenomenological approach, in order to understand the lived experiences of the pesantren community in the process of academic reform, including the dynamics, debates, and contradictions within it. The research was conducted at Ponpes Autis Achsaniyah Kudus using data collection methods such as interviews, observations, and documentation. Data analysis adopted the qualitative analysis model by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings of the study indicate that pesantren, with its tradition of openness (inclusivity) and respect for human rights (humanitas), is capable of providing the inclusive education needed by society and serving as an effective platform to realize inclusive education within the community.